Autonomic response to fetal acidosis using an experimental sheep model. (March 2020) - Vanspranghels, Roxane; De Jonckheere, Julien; Drumez, Elodie; Lauriot dit Prevost, Arthur; Sharma, Dyuti; Ghesquiere, Louise; Storme, Laurent; Houfflin-Debarge, Véronique; Garabedian, Charles
Abstract: Background: The autonomic nervous system has a major role in fetal adaptation to hypoxia. Its activity might be assessed using heart rate variability and heart rate deceleration analyses. Objective: To evaluate the ability of different heart rate variability and morphological deceleration analyses to predict fetal acidosis during labor in an experimental fetal sheep model. Study Design: Repeated 1-minute total umbilical cord occlusions were performed at mild (1minute every 5 min), moderate (1 min every 3 min), and severe (1 min every 2 min) umbilical cord occlusion periodicities until arterial pH reached 7.10. Hemodynamic, blood gas analysis, morphological analysis of decelerations (magnitude, slope, and area ofdecelerations), and heart rate variability parameters were recorded throughout the experiment.Heart rate variability analysis included temporal analysis (root mean square of successivedifferences between adjacent RR intervals, standard deviation of normal to normal RR intervals, short term variability), spectral analysis (low frequencies, high frequencies, normalized high frequencies), and a new index developed by our team, the Fetal Stress Index.We defined and compared three pH groups: >7.20, 7.10–7.20, and <7.10. Results: Eleven experiments were performed. Repetitive umbilical cord occlusions resulted in progressive fetal acidosis. Fetal Stress Index was correlated with pH and lactate (p < 0.05) and increased with acidosis. There were no significant correlations between pH, lactate, and other indices (spectral analysis, temporal analysis, or morphological analysis of decelerations). Conclusion: This protocol allowed us to identify the progressive onset of fetal acidosis in an experimental model close to labor. Fetal Stress Index is a heart rate variability method that varies with acidosis and indicates an increase in parasympathetic nervous system activity in response to fetal acidosis.